2007
DOI: 10.1117/12.773366
|View full text |Cite
|
Sign up to set email alerts
|

Solar hydrogen production by tandem cell system composed of metal oxide semiconductor film photoelectrode and dye-sensitized solar cell

Abstract: Photocatalytic and photoelectrochemical approaches to solar hydrogen production in our group were introduced. In photocatalytic water splitting system using NiO x / TiO 2 powder photocatalyst with concentrated Na 2 CO 3 aqueous solution, solar energy conversion efficiency to H 2 and O 2 production (STH efficiency) was 0.016%. In addition, STH efficiency of visible light responding photocatalyst, NiO x / promoted In 0.9 Ni 0.1 TaO 4 , was estimated at 0.03%. In photoelectrochemical system using an oxide semicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The photoanode/DSSC combination was first suggested by Augustynski and Graẗzel 104 with WO 3 as the photoanode suggesting that device would be capable of 4.5% η STH based on the plateau photocurrent (J pl ) of WO 3 . 105 In practice, tandem devices with WO 3 have been constructed by Park and Bard 106 and Arakawa et al 107 giving η STH 's up to 2.8% at AM 1.5G (100 mW cm −2 ) using Pt as the cathode. However, similar to the a-Si based devices, two DSSCs connected in series to the photoanode were necessary to afford overall water splitting.…”
Section: Photoanode/photovoltaic Tandem Cellsmentioning
confidence: 99%
“…The photoanode/DSSC combination was first suggested by Augustynski and Graẗzel 104 with WO 3 as the photoanode suggesting that device would be capable of 4.5% η STH based on the plateau photocurrent (J pl ) of WO 3 . 105 In practice, tandem devices with WO 3 have been constructed by Park and Bard 106 and Arakawa et al 107 giving η STH 's up to 2.8% at AM 1.5G (100 mW cm −2 ) using Pt as the cathode. However, similar to the a-Si based devices, two DSSCs connected in series to the photoanode were necessary to afford overall water splitting.…”
Section: Photoanode/photovoltaic Tandem Cellsmentioning
confidence: 99%
“…The products of these oxidations are either CO 3 •– or C 2 O 6 2– . Indeed, several studies have pointed out that the presence of HCO 3 – /CO 3 2– in the system catalyzes photochemical water oxidation. ,, Furthermore, it has been shown that photochemical oxidation of SO 2 in aqueous media is enhanced by the presence of carbonate . It was proposed that the formation of CO 3 •– is involved.…”
Section: Photocatalysismentioning
confidence: 99%
“…In practice, tandem devices with WO 3 have been constructed by Park and Bard 126 and Arakawa et al 127 However, similar to the a-Si-based devices, two DSSCs connected in series to the photoanode were necessary to afford overall water splitting. This was accomplished by positioning these two DSSCs side by side behind the WO 3 photoanode.…”
Section: Pec/dssc Tandem Cellsmentioning
confidence: 99%